Ethanolic Garlic Extract (Allium sativumL) Increased Viability and Proliferation of Human Gingival Fibroblast In Vitro (Bangladesh Journal of Medical Science, 2018)
Introduction: Garlic is a natural herb which can be used to be a good alternative treatment because cheap and safe. Garlic contains allicin which may has act antibacterial and antiinflammatory effect. Moreover, garlic extract has a good biocompatibility and can stimulate cell growth. Does garlic extract biocompatible and can stimulate cell growth that is seen from the proliferation of human gingival fibroblasts and how its work will be studied.Objective: The aim of this study was to analyze the biocompatibility of garlic extract by observing the viability and proliferation of human gingival fibroblasts in vitro.Methods: Biocompatibility test was conducted using serial concentration of garlic extract. Human gingival fibroblasts was seeded into 96 microwell plate with density of 2x103 cells, added with the fourteen serial concentration of garlic extract, and incubated in 37o C and 5% CO2for 24, 48 and 72 hours. MTT assay was used to analyze the viability and proliferation of human gingival fibroblasts. Data were analyzed by the Kruskal Wallis and U Mann-Whitney test.Results: The result showed that in each time of observation, there is no significant difference in viability fibroblast (p>0,05), but there are significant difference between time of observation at 24, 48, and 72 hours (p